Jesus loves you and evolution is true : why youth ministry needs science - Tolsma, Sara Sybesma; Lief, Jason (Fortress Press, 2019)
Science is not a threat to the faith of Christian youth. In fact, Sara Sybesma Tolsma, an award-winning scientist, and Jason Lief, a leading practical theologian, argue that youth ministry needs science to help young people explore their relationship to God and engage their world faithfully. Pastors, faith leaders, and youth workers must not only engage science but embrace its lessons for the life and practice of Christian faith today.